2020
DOI: 10.3897/neotropical.15.e59000
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation structure as the main source of variability in scorpion assemblages at small spatial scales and further considerations for the conservation of Caatinga landscapes

Abstract: Even at the local scale, environmental changes due of anthropogenic actions represent a source of disturbance in terrestrial ecosystems, forcing species to respond according to their ecological plasticity. Thus, stenotopic species and those with low-dispersal ability will likely be negatively affected by landscape modifications that reduce environmental complexity. In this study, we identify and quantify the effects of biotic and abiotic factors related to habitat complexity on the variation in scorpion assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Moreover, in the case of Egyptian drylands, these areas are known for their high geological, environmental, and climatic heterogeneity (Boulos 2009;Zahran and Willis 2009). Therefore, such environmental heterogeneity is expected to affect the maintenance of scorpion assemblages, as already observed in a seasonally dry tropical forest in Brazil (Foerster et al 2020;Lira et al 2021a). By analogy, the landscape heterogeneity observed in Egypt may allow the In terms of dβ patterns, the relative importance of their components may be interpreted as an essential proxy for understanding the dispersal capabilities of the studied species (Baselga 2010).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Moreover, in the case of Egyptian drylands, these areas are known for their high geological, environmental, and climatic heterogeneity (Boulos 2009;Zahran and Willis 2009). Therefore, such environmental heterogeneity is expected to affect the maintenance of scorpion assemblages, as already observed in a seasonally dry tropical forest in Brazil (Foerster et al 2020;Lira et al 2021a). By analogy, the landscape heterogeneity observed in Egypt may allow the In terms of dβ patterns, the relative importance of their components may be interpreted as an essential proxy for understanding the dispersal capabilities of the studied species (Baselga 2010).…”
Section: Discussionmentioning
confidence: 94%
“…Again, the scarcity of information about the ecology of scorpions inhabiting desert ecosystems in northern Africa is a strong limiting factor that prevents us from providing a clearer description of how and to what extent the climate affects the distribution of scorpion species in the area. However, a few examples of how vegetation structure plays a vital role in defining community parameters (notably species richness) in scorpion assemblages have been reported elsewhere: species richness is positively related to shrub cover in a North American desert (Polis and McCormick 1987); species abundance and composition covary with vegetation density in some Neotropical semi-arid regions (Foerster et al 2020; Lira et al 2021a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Lira et al (2021a) detected that vegetation cover (biotic variable) is a key factor to scorpion diversity in a Brazilian Atlantic Rainforest. In addition, vegetation structure also plays a role to maintenance of scorpion assemblage on Seasonal Dry Tropical Forest (Foerster et al, 2020;Lira et al, 2021b). At the regional scale, Lira et al (2019a) investigated the effect of the bioclimatic gradient between wet and dry forests on scorpion assemblages in Brazil and found that temperature and precipitation (abiotic variables) were the major explanatory factors of scorpion richness and dβ, which increased toward the dry forest gradient.…”
Section: Introductionmentioning
confidence: 99%